Public discussion between John Brindley and Robert Owen, on the questions, "What is socialism; and what would be its practical effects upon society ?" : held in the Amphitheatre, Bristol, on the Evenings of January 5th, 6th, and 7th, 1841 ; Moderator, John Scandrett Harford, - Owen, Robert (1771-1858)
Printed without correction by either party, from the verbatim report of the short-hand writers engaged expressly for the purpose; with an appendix containing an address from the Moderator, the Chairman of the Committee of Management, and from Mr. Brindley.